Non-Identical Twins – Microglia and Monocyte-Derived Macrophages in Acute Injury and Autoimmune Inflammation - Schwartz, Michal; Jung, Steffen (Frontiers in Immunology, 2012)
The brain has been commonly regarded as a ‘tissue behind walls’. Appearance of immune cells in the brain has been taken as a sign of pathology. Moreover, since infiltrating monocyte-derived macrophages and activated resident microglia were indistinguishable by conventional means, both populations were regarded together as inflammatory cells that should be mitigated. Yet, because the microglia permanently reside in the brain, attributing to them negative properties evoked an ongoing debate; why cells that are supposed to be the brain guardians acquire only destructive potential. Studies over the last two decades in the immune arena in general, and in the context of central nervous system (CNS) pathology in particular, have resulted in a paradigm shift towards a more balanced appreciation of the contributions of immune cells in the context of brain maintenance and repair, and towards the recognition of distinct roles of resident microglia and infiltrating monocyte-derived macrophages. The understanding that the origins of the resident microglia are distinct from monocyte-derived cells, and the notion that monocyte-derived macrophages are hardly seen in the healthy brain and infiltrate to the injured CNS for facilitating its recovery